Namibia Systematic Country Diagnostic - World Bank (World Bank, Washington, DC, 2021)
Since gaining independence in 1990, Namibia has undertaken an economic transformation and experienced strong economic growth. Despite decades marked by progress, deep underlying challenges remain in Namibia, undermining the prospects for further advancement. Namibia has been in recession since 2016 and public finances have continued to deteriorate. The global COVID-19 crisis is expected to have a substantial adverse economic and social impact.